Utilization of Google Earth to Identify Building Density - Bagus Setyo Widhiarto; Pranichayudha Rohsulina; Ary Wijayanti (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Land-use change is now common due to human activities, including economic, social, and cultural activities. Areas transforming for economic, social, and cultural purposes experience changes in land use, leading to a transition from green open spaces to buildings and resulting in hot daily surface temperatures due to a lack of vegetation. The purpose of this study is to examine the changes in built and non-built land in the Kartasura District. This study examines the relationship between surface temperature, vegetation, and building levels by using NDVI, NDBI, and ESG analysis, which is processed using the Google Earth Engine programming language. This study uses a qualitative descriptive method with a spatial approach, one of the approaches in the field of geography. The spatial approach in this study is more emphasized on spatial process analysis. The results indicate that there is a correlation between high surface temperature and low vegetation density, as well as high building density.